PENGARUH DOSIS NPK DALAM MENINGKATKAN PERTUMBUHAN SEMANGKA DI GUNUNG SELAMAT, KECAMATAN BILAH HULU, KABUPATEN LABUHAN BATU - Toni Suganda; Siti Hartati Yusida Saragih; Fitra Syawal Harahap; Dini Hariyati Adam (Fakultas Pertanian, Universitas Janabadra, 2023)
on January 2023 until completion. application of NPK fertilizer was given at 2 WAP using 4 treatment levels, namely: P1:80 g/plant P2:120 g/plant P3:160 g/plant. Parameters observed were plant length, number of leaves, flowering age, were observed at 2 WAP until the end of the vegetative period using a meter from the base of the stem to the tip of the root. From the results of this study the growth of watermelon plants, plant length and amount of leaves were calculated from the age of 2, and 4WAP and the flowering age was taken when the plants began to flower and from this study shows that the correct dose of NPK fertilizer for the growth and yield of watermelon plants is 160 g/plant. This reserch showed thtof NPK fertilizer the growth of watermelon plants both from plant length, number of leaves is 160 g/plant. Keywords: Fertilizer, Horticulture, PlantINTISARI Penelitian ini akan dilaksanakan dikebun percobaan Gunung Selamat, Bilah hulu, Labuhanbatu pada bulan Januari 2023 sampai selesai. pengaplikasian pupuk NPK diberikan pada 2 MST dengan menggunakan 4 taraf perlakuan yaitu: P1 :80 g/tanaman P2:120 g/tanaman P3:160 g/tanaman. Pada penelitin ini menggunakan nilai panjang batng, jumlah daun, umur bunga pada 2 MST hingga akhir vegetatif alat ukur panjang dari pangkl akar ke ujung batang. Dari hasil penelitian ini pertumbuhan tanaman semangka panjang tanaman dan jumlah daun dihitung sejak umur 2, dan 4 MST dan umur berbunga diambil pada saat tamanan mulai berbunga. Hasil melaporkan bahwa perlakuab 160 g/tanaman memberikan hasil terbaik dari seluruh parameter. Kata Kunci: Pupuk, Hortikultura, Tanaman